Evaluation of Serum High Sensitivity C-reactive Protein (hs-CRP) In Type-2 Diabetic Patient - Haque, AKM Fazlul; Ekram, ARM Saifuddin; Islam, Quazi Tarikul; Jahan, Md Sarwar; Haque, Md Zahirul (Journal of Medicine, 2010)
Type-2 diabetes may remain in subclinical form for years before diagnosis. This quiescence of type-2 diabetes is a great concern for health care providers. The earliest change of the type-2 diabetes is the insulin resistance, which is associated with the increased macrovascular risk due to induction of chronic inflammation in the vessels of the body which leads to atherosclerotic change in the vessels. High sensitivity CRP (hs-CRP) is the measure of C-reactive protein with greater accuracy and the lower limit of its assay is .01 mg/L which is more than 100 times as sensitive as the usual CRP measurement (lower limit 5 mg/L). The median level of hs-CRP from blood samples of apparent healthy subjects is 0.8 mg/L. For this, physician uses the hs-CRP parameter as a marker of chronic inflammation in apparently normal healthy individuals, specially for the assessment of atherosclerosis, which is a chronic inflammatory procedure from the very beginning, in type-2 diabetic, obese and hypertensive patients. This vascular atherosclerosis assessment help them to calculate the cardiovascular as well as cerebrovascular risk of those patients. To help the type-2 diabetic patients from the very begining in respect of the prognostic view of the macrovascular risk, estimations of serum hs-CRP in the early stage of these patient may be a enthusiastic one. This descriptive study was carried out by choosing 70 diabetic patient who had no other comorbidity or any complications of diabetes and 35 healthy subjects who were neither diabetic nor had any diseases. Both the groups were non-smoker and non-alcoholic and non-hypertensive, hs-CRP level was measured in both the groups along with the HbA1c%. The mean hs-CRP in diabetic group was 1.13 mg/L and in normal healthy subjects was 0.39 mg/L. This higher level of mean hs-CRP (1.13 mg/L) in diabetic patients is statisticaly significant (P<0.01) compared with that of the normal healthy subjects mean hs-CRP (0.39 mg/L). This mean level of hs-CRP in normal healthy subjects was below the lower level of cardiovascular risk (1 mg/L). Keywords: High sensitivity CRP, C-reactive protein, diabetes DOI:10.3329/jom.v11i1.4263 J Medicine 2010: 11: 20-23